Individual and Network Correlates of Antisocial Personality Disorder Among Rural Nonmedical Prescription Opioid Users. Issue 2 (12th May 2016) - Smith, Rachel V.; Young, April M.; Mullins, Ursula L.; Havens, Jennifer R.
Abstract: Purpose: Examination of the association of antisocial personality disorder (ASPD) with substance use and HIV risk behaviors within the social networks of rural people who use drugs. Methods: Interviewer‐administered questionnaires were used to assess substance use, HIV risk behavior, and social network characteristics of drug users (n = 503) living in rural Appalachia. The MINI International Psychiatric Interview was used to determine whether participants met DSM‐IV criteria for ASPD and Axis‐I psychological comorbidities (eg, major depressive disorder, posttraumatic stress disorder, generalized anxiety disorder). Participants were also tested for herpes simplex 2, hepatitis C, and HIV. Multivariate generalized linear mixed modeling was used to determine the association between ASPD and risk behaviors, substance use, and social network characteristics. Results: Approximately one‐third (31%) of participants met DSM‐IV criteria for ASPD. In multivariate analysis, distrust and conflict within an individual's social networks, as well as past 30‐day use of heroin and crack, male gender, younger age, lesser education, heterosexual orientation, and comorbid MDD were associated with meeting diagnostic criteria for ASPD. Conclusions: Participants meeting criteria for ASPD were more likely to report recent heroin and crack use, which are far less common drugs of abuse in this population in which the predominant drug of abuse is prescription opioids. Greater discord within relationships was also identified among those with ASPD symptomatology. Given the elevated risk for blood‐borne infection (eg, HIV) and other negative social and health consequences conferred by this high‐risk subgroup, exploration of tailored network‐based interventions with mental health assessment is recommended.